Variação nictemeral da comunidade zooplanctônica no reservatório da UHE de Furnas (compartimento do rio Sapucaí) - Silva, Erika Dos Santos (2015)
The variations that occur in tropical reservoirs, both physical and chemical standards as the biological communities, can occur in a short period of time, such as in a range of 24 hours (diurnal). Stratification and thermal destratification in aquatic environments are important ecological factors in vertical organization and seasonal reorganization of zooplankton. This study aims to verify the influence of diurnal variation in the zooplankton community structure at one point in Furnas HPP reservoir (arm Sapucai, 21ºS 22'16 "and 00'06 46ºW"), linking the community of vertical variation patterns the physical and chemical parameters over a diurnal cycle. The collections was held on January 15, 2014, during a period of 24 hours in 3-hour intervals at depths of 0m, 2m, 4m, 6m, 8m and 9m, using a bottle of Van Dorn with 5L capacity. Simultaneously, measurements were made of the physical, chemical and biological variables. Thermal and chemical stratification were observed throughout the day and no homogenization throughout the water column. The surface of the water column was well oxygenated (10.5 mg l-1), while in the background were recorded close to zero, reaching close to anoxia (0.75 mg L-1). The pH remained in acid and alkaline bottom surface (5.46 to 8.96), and the electric conductivity was low at the surface (about 50 μS.cm-1) and high in the bottom (90 μS. cm-1) due to sedimentation of particles and increased decomposition rates in that region. Stratification represented a barrier to zooplankton, preventing migration and the homogenization of the distribution of these organisms. Most of the species remained on the surface of the water column and only for some species of Cladocera was subject to the normal pattern of migration (Ceriodaphnia silvestrii, Ceriodaphnia cornuta cornuta and Ceriodaphnia cornuta rigaudi). For species of Copepoda group, the spatial separation was seen as a way to avoid interspecific competition and predation of adults with eggs, a strategy for the maintenance of the species itself. The most accepted hypothesis to explain the migration pattern recorded in this study is that predation has influenced the migratory behavior and the distribution of zooplankton species.